Prevalence and Pattern of Rheumatic Heart Disease among Reproductive Age Group Female - Shrestha, Manoj; Aryal, Prakash (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Rheumatic heart disease (RHD) remains a major public health problem in developing countries. In low income countries RHD accounts for approximately 90% of all cardiovascular disease among pregnant women. This study aims to evaluate the prevalence and pattern of RHD among reproductive age group women presenting to a tertiary care teaching hospital in Central Nepal. MATERIAL AND METHODS Prospective observational study was carried out in College of Medical Sciences Teaching Hospital, Bharatpur, Nepal from January 2019 to December 2019 by doing transthoracic echocardiography (TTE) of reproductive age group females (n=800) from 15 years to 45 years of age. The data were collected in pre-structured proforma. RESULTS Out of 800 patients, RHD was present in 46 (5.75%) patients. The incidence of RHD was found to be highest in the age group of 30-35 years 13 (28.3%) and the mean age of presentation was 29.24 years. Mitral valve was the most common valve involvement and mitral regurgitation 37 (80.4%) was the most common valvular dysfunction present in patients with RHD. CONCLUSION The prevalence of RHD among reproductive age group female is high and mitral valve is the most commonly affected valve.